FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU PETANI DALAM MENERIMA PROGRAM KAWASAN RUMAH PANGAN LESTARI (KRPL) DI KABUPATEN PELALAWAN - Rahmi Puspita Sari; Rosnita Rosnita; Roza Yulida (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2016)
The aims of this research are: (1) To determine the implementation of KRPL Programs,  (2)  To  analyzing  dominant  indicator  and  influence  of  characteristic  of innovation,  communication  channels,  agent  of  change,  community  leaders  and characteristic  farmers.  The  research  was  conducted  in  11  villages  of  Pelalawan Regency in 2013. The population is manager and members of farmers as 360 people which were taken 174 people as samples. The method used is descriptive analysis and Structural  Equation  Models  (SEM).  The  research  showed  implemention  of  KRPL program in Pelalawan regency accepted Rp. 47.000.00 for each group. The coast was spent  for  environment  industry  like  the  source  of  food  or  cattle  and  fish.The  most dominant indicator that influences characteristic of innovation is concord of program, for communication channel is social media, for agent of change is keep the program and  prevent  it  from  any  sticking,  for  community  leaders  is  to  educator  and  the characteristic of farmer is subsistence level. Farmers habit in deciding the dominant is using confirmation step. The most influent variable of farmers habit is characteristic innovation.